2021
DOI: 10.1111/jfd.13357
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR for Tenacibaculum dicentrarchi and T. finnmarkense

Abstract: Numerous Tenacibaculum species, including T. dicentrarchi, T. maritimum and T. finnmarkense, are associated with tenacibaculosis in finfish; however, quantitative identification techniques are limited. Quantitative PCR assays were developed to detect T. dicentrarchi and T. finnmarkense. TaqMan assays using 16S rDNA demonstrated low detection limits (0.07–269 bacteria), suitable amplification efficiencies (>86%) and moderate specificity. However, the amplification of isolates with 100% sequence similarity to T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Prior research into aquatic pathogens has shown that cycle quotients from qPCR assays can differentiate disease states of fish and determine thresholds of bacteria required to cause infection, where similar applications have occurred for salmon gill poxvirus [19] and bacterial coldwater disease [20]. However, the qPCR assays developed by a previous study [7], which were used in the present study, are not suitable for determining such a threshold in uncontrolled conditions as there are limitations relating to the specificity and copy number for the 16S rDNA gene in Tenacibaculum. For Tdic, mortality of exposed fish within 48 h is similar to [4] and may indicate that the results of the Tdic exposure are not solely based on the bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior research into aquatic pathogens has shown that cycle quotients from qPCR assays can differentiate disease states of fish and determine thresholds of bacteria required to cause infection, where similar applications have occurred for salmon gill poxvirus [19] and bacterial coldwater disease [20]. However, the qPCR assays developed by a previous study [7], which were used in the present study, are not suitable for determining such a threshold in uncontrolled conditions as there are limitations relating to the specificity and copy number for the 16S rDNA gene in Tenacibaculum. For Tdic, mortality of exposed fish within 48 h is similar to [4] and may indicate that the results of the Tdic exposure are not solely based on the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to transport to the Centre for Innovation in Fish Health (CIFH), at Vancouver Island University in Nanaimo (BC), the salmon population was screened for and tested negative for infectious salmon anemia virus, infectious pancreatic necrosis virus, and piscine orthoreovirus. Water from the recirculating aquaculture systems (RAS) systems at the CIFH, were tested using qPCR for Tmar, Tdic, and Tfinn prior to the introduction of fish following previously developed protocols [7].…”
Section: Fish Husbandrymentioning
confidence: 99%
See 3 more Smart Citations